Women’s collectives and social support: exploring pathways and impacts among forcibly displaced women - Seff, Ilana; Meinhart, Melissa; Sarraf, Danielle; Abu Zuhair, Amna; Sofia, Jacqueline; Atuheire, Racheal; Lee, Jessica; Ahmed, Nimo; Poulton, Catherine; Stark, Lindsay (Frontiers in Sociology, 2024)
BackgroundDuring humanitarian crises, women face both heightened vulnerabilities and a disruption to their social networks. Previous research points to the positive impact of women’s collectives in low-income settings, but less is known about the distinct forms, mechanisms, and consequences of the social support that emerges from these collectives, particularly for women affected by conflict. Recognizing the importance of social support in such contexts, this study utilizes the photovoice methodology to examine the dynamics of social support across women’s collectives in three distinct settings.MethodsThis study recruited forcibly displaced women participating in women’s collectives in Indonesia (n = 5), Jordan (n = 12), and Uganda (n = 11). Photovoice, a participatory research method that centers the voices of study participants, was implemented across 7–8 sessions in each setting. Participants took photographs in response to four prompts and then discussed their pictures and lived experiences related to social support in facilitated discussion groups. Transcripts were analyzed using thematic analysis and a mixed inductive and deductive approach.ResultsAcross all study sites, participants highlighted the importance of five types of informal social support: emotional, instrumental, informational, companionship, and esteem support. Emotional support, one of the most prominently mentioned forms, served to buffer against stressors and enhance mental well-being. Instrumental and informational support facilitated meeting basic needs, accessing resources, and, in Uganda, improving members’ physical safety. Companionship support fostered a sense of belonging and shared identity, while esteem support validated members’ perspectives and aspirations and bolstered self-worth. In the Jordan collective, esteem support proved especially beneficial in countering the marginalization members experienced in their community.DiscussionFindings underscore the critical role of women’s collectives in providing diverse forms of social support to foster empowerment, agency, and resilience among forcibly displaced women. By centering the voices of participants and employing survivor-centered approaches like photovoice, this study amplifies the perspectives of women within these collectives, contributing to more inclusive and responsive humanitarian interventions. Future research should continue prioritizing women’s experiences and research questions, ensuring that interventions address their needs effectively.